2020
DOI: 10.3390/nano10112310
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Breast Cancer-Bearing BALB/c Mice with Magnetic Hyperthermia using Dendrimer Functionalized Iron-Oxide Nanoparticles

Abstract: The development of novel nanoparticles for diagnostic and therapeutic applications has been one of the most crucial challenges in cancer theranostics for the last decades. Herein, we functionalized iron oxide nanoparticles (IONPs) with the fourth generation (G4) of poly amidoamine (PAMAM) dendrimers (G4@IONPs) for magnetic hyperthermia treatment of breast cancer in Bagg albino strain C (BALB/c)mice. The survival of breast cancer cells significantly decreased after incubation with G4@IONPs and exposure to an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…Current research progress on nanotechnology has led to the development of nanocarrier-drug delivery vehicles and their potential applications in gene delivery and cancer therapy [ 8 , 9 , 10 ]. Superparamagnetic nanoparticles (NPs) (SPIONs) have emerged as a superior agent in tumor therapy because of their unique properties, particularly the superior magnetism that permits non-invasive magnetic resonance imaging (MRI) and in vivo applications such as cancer tissue hyperthermia by a targeted technique in the presence of an external magnetic field [ 11 , 12 , 13 , 14 , 15 ]. This field promotes the cellular uptake of NPs containing magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Current research progress on nanotechnology has led to the development of nanocarrier-drug delivery vehicles and their potential applications in gene delivery and cancer therapy [ 8 , 9 , 10 ]. Superparamagnetic nanoparticles (NPs) (SPIONs) have emerged as a superior agent in tumor therapy because of their unique properties, particularly the superior magnetism that permits non-invasive magnetic resonance imaging (MRI) and in vivo applications such as cancer tissue hyperthermia by a targeted technique in the presence of an external magnetic field [ 11 , 12 , 13 , 14 , 15 ]. This field promotes the cellular uptake of NPs containing magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…After this the wells were washes with warm PBS, and and fresh tissue culture media added. Gap filling was measured using the CytoSmart ® Live Image System (Piet Heinstraat, Zutphen, Holland) [ 12 ]. The gap area at 0 h and 24 h were measured with ImageJ ® software and the relative migration was calculated using Equation (1) as seen below.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of such studies have shown that AuNPs have inhibitory effects on cancer cell migration without impacting on the viability of these cells which makes it a promising candidate for further application in gold nanoparticle aided radiotherapy (GNRT) [ 6 , 7 , 8 , 9 ]. Additionally, metallic nanoparticles have been used to enhance other cancer treatments methods such as magnetic hyperthermia and phototherapy [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides their magnetism, MNPs show biocompatibility, chemical stability and dispersibility, and the possibility to be further functionalized thanks to the smart addition of different coatings in their surfaces. Since their approval to be used in humans by the Food and Drug Administration (FDA) in the United States and the European Commission in Europe, iron oxide nanoparticles have played a very important role in in-vivo diagnosis, separation, concentration, and/or manipulation of different components in some samples, i.e., blood or body fluids [ 6 , 7 ], contrast agents in magnetic resonance imaging (MRI) [ 8 , 9 ], or tracers in magnetic particle imaging (MPI) [ 10 , 11 ], as well as heating agents in magnetic field assisted hyperthermia [ 12 , 13 , 14 , 15 , 16 ] or drug carriers in magnetic drug targeting and magnetic gene therapies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%